Design and Manufacture Indirect Method Grain Bed Dryer with 10 Kg Capacity Fueled by Wasted Oil - Rizki Cakrawiguna; Noviyanti Nughraha; Nuha Desi Anggraeni (Department of Mechanical Engineering, Universitas Andalas, 2022)
Artificial grain dryers use additional heat to dry the grain, the energy source for this machine is fuel, gas, husks, and firewood. The dryer used in this study uses wasted oil with the indirect method. This grain dryer with wasted oil helps us make the environment stay clean. The purpose of this research is to design and manufacture a bed dryer type grain dryer with a capacity of 10 kg fueled by wasted oil, with the target of drying grain to a moisture content of 13-14%, dry grain is odorless, the drying cost is relatively cheap because it uses used lubricating oil. The machine is made by the selected design. Including bed dryer, plenum chamber, hot air duct, heater box, stove, oil reservoir, and oil line. The results of the design and manufacture obtained bed dryer dimensions and plenum space 120x50x100cm, a cylindrical stove with a diameter of 20cm and a height of 20cm which is connected by a channel to an oil reservoir with a maximum capacity of 30 liters. This tool succeeded in drying grain from 30% and 38% to 13% moisture. Heating uses indirect or indirect methods so that the air that heats the grain does not contain oil. The heated grain is clean and does not smell of oil